2010
DOI: 10.1080/10810730.2010.522691
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Provider–Patient Communication and Trust in Online Sources in Internet Use for Health-Related Activities

Abstract: Provider-patient communication is an important factor influencing patients' satisfaction and health outcomes. This study draws upon the uses and gratification theory to examine how individuals' perception of communication with healthcare providers is associated with their Internet use for health-related activities. Using the data from the 2007 Health Information National Trends Survey (HINTS), we found that as individuals perceived their communication with providers to be less patient-centered, they were more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
118
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(121 citation statements)
references
References 40 publications
2
118
0
1
Order By: Relevance
“…3 Because physicians no longer serve as the sole gatekeepers of health information, a large proportion of patients with Internet access but limited health literacy are attempting to meet their health information needs with available online health resources. 38 Each readability analysis evaluates different aspects of the articles we collected ( Table 2). The Fry Graph, which plots the average number of sentences and the average number of syllables per 100 words to determine grade level, reveals that most of the articles assessed fall between the high school and college levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3 Because physicians no longer serve as the sole gatekeepers of health information, a large proportion of patients with Internet access but limited health literacy are attempting to meet their health information needs with available online health resources. 38 Each readability analysis evaluates different aspects of the articles we collected ( Table 2). The Fry Graph, which plots the average number of sentences and the average number of syllables per 100 words to determine grade level, reveals that most of the articles assessed fall between the high school and college levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, trust in media has also been associated with health-related outcomes. For example, researchers have found that trust in mass media was significantly associated with self-rated good health, seeking more information online and interpersonal communication (Hou & Shim, 2010;Huh, DeLorme, & Reid, 2005;Tokuda, Fujii, Jimba, & Inoguchi, 2009). Therefore, this study will extend the literature by exploring how trust in a health-related social networking site is associated with health-related outcomes.…”
Section: Online Health Informationmentioning
confidence: 95%
“…It is necessary to understand what lead individuals to use this particular source for food recall information, instead of alternative sources (Hou & Shim, 2011;Kivits, 2004). Also as shown by the U.S. data in this study, popularity varied across specific social media tools, including SNSs, newsletters, listervs, email alerts, RSS feeds and micro-blogs.…”
Section: ) Theoretical Implicationsmentioning
confidence: 86%
“…It is plausible that some deficits in resources in a face-to-face context were not barriers to active use of social media for food recalls, but they were rather motivators to use a more engaging communication tool (Han et al, 2012). Risk perception (Rimal & Real, 2003) and perceived trustworthiness of the Internet and that of health professionals (Hou & Shim, 2011;Kivits, 2004) also deserve attention as primary predictors of social media use for food risk information in Korea.…”
Section: ) Theoretical Implicationsmentioning
confidence: 99%